2007
DOI: 10.4141/cjps06019
|View full text |Cite
|
Sign up to set email alerts
|

Acetolactate synthase inhibitor-resistant stinkweed (Thlaspi arvense L.) in Alberta

Abstract: G. 2007. Acetolactate synthase inhibitor-resistant stinkweed (Thlaspi arvense L.) in Alberta. Can. J. Plant Sci. 87: 965-972. Two stinkweed populations from southern and central Alberta were not controlled by acetolactate synthase (ALS)-inhibiting herbicides in 2000. This study reports on their cross-resistance to ALS-inhibiting herbicides, molecular basis of resistance, and inheritance of resistance. Both putative herbicide-resistant biotypes responded similarly to increasing doses of the herbicides. The biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…ALS activity assays showed that R white mustard plants required a tribenuron-methyl concentration 2,777 times higher than S plants for similar inhibition of ALS activity (I 50 ). A similar insensitivity of ALS to tribenuron-methyl among R biotypes was exhibited in flixweed resistant to tribenuron-methyl in China (Xu et al 2010) and to other ALS-inhibiting herbicides in field pennycress (Thlaspi arvense L.) (Beckie et al 2007), and prickly lettuce (Lactuca serriola L.) (Preston et al 2006).…”
Section: Resultsmentioning
confidence: 54%
“…ALS activity assays showed that R white mustard plants required a tribenuron-methyl concentration 2,777 times higher than S plants for similar inhibition of ALS activity (I 50 ). A similar insensitivity of ALS to tribenuron-methyl among R biotypes was exhibited in flixweed resistant to tribenuron-methyl in China (Xu et al 2010) and to other ALS-inhibiting herbicides in field pennycress (Thlaspi arvense L.) (Beckie et al 2007), and prickly lettuce (Lactuca serriola L.) (Preston et al 2006).…”
Section: Resultsmentioning
confidence: 54%
“…plants with substitution of Pro 197 by Ala, Arg, Gln, Leu and Ser were highly resistant to sulfometuron but not cross‐resistant or with a low level of cross‐resistance to imazapyr 24. In addition, the substitution of Pro 197 by Leu in two populations of field pennycress [ Thlaspi arvense (L.)] led to high resistance to ethametsulfuron but no cross‐resistance to florasulam 25. However, in contrast to these findings, an R redroot amaranth [ Amaranthus retroflexus (L.)] biotype with substitution of Pro 197 by Leu was resistant to sulfonylureas (RF = 6–127) and cross‐resistant to imidazolinones (RF = 4–63), triazolopyrimidines (RF = 20–35) and pyrimidinyl(thio)banzoates (RF = 11) 26.…”
Section: Resultsmentioning
confidence: 99%
“…Wild radish (Raphanus raphanistrum L.) populations also had point mutations of proline 197 to four different amino acid substitutions: histidine, threonine, alanine, and serine (Yu et al 2003;Walsh et al 2007). Proline 197 substitution by leucine was reported in ALS inhibitor-resistant stinkweed (Thlaspi arvense L.) populations (Beckie et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…To date, ALS resistance in field-selected weed populations are conferred by 22 amino acid substitutions at seven sites in the ALS gene, which are alanine 122 (Ala 122 ), proline 197 (Pro 197 ), alanine 205 (Ala 205 ), aspartate 376 (Asp 376 ), tryptophan 574 (Trp 574 ), serine 653 (Ser 653 ), and glycine 654 (Gly 654 ) (Tranel and Wright 2002;Tranel et al 2010;Whaley et al 2007; recently reviewed by Powles and Yu [2010]). Eleven substitutions have been reported for Pro 197 (Ala, Arg, Gln, His, Ile, Leu, Lys, Met, Ser, Thr, and Trp) (Beckie et al 2007;Cui et al 2008;Powles and Yu 2010;Tranel and Wright 2002;Tranel et al 2010;Warwick et al 2008;Yu et al 2003Yu et al , 2010, and these single substitutions usually result in a high level of resistance to sulfonylurea herbicides.…”
mentioning
confidence: 99%